Madrasah Principal Leadership in the Digital Era: A Literature Review of Challenges and Strategies - Akramul Huda; Gusnita; Sri Atikah; Aprizal Ahmad; Rully Hidayatullah (Konsultan Jurnal Ilmiah Indonesia, 2026)
The development of digital technology has brought significant changes to the education system, including in the management of madrasahs. However, digital transformation in madrasahs still faces various challenges, such as low teacher digital literacy, limited technological infrastructure, and weak digital leadership competencies. This study aims to analyze the leadership challenges of madrasah principals in the digital era, examine effective leadership strategies, and identify relevant leadership models for the transformation of Islamic education. This study uses a literature review method with a qualitative descriptive approach through the analysis of various scientific articles indexed by Scopus and SINTA relevant to the research topic. Data were analyzed using content analysis techniques to produce a systematic, valid, and credible synthesis of findings based on trusted scientific sources. The results show that effective madrasah principal leadership in the digital era is adaptive leadership that integrates transformational leadership, digital competence, and Islamic values. The strategies implemented include improving teachers' digital competence, digitizing administration, strengthening digital literacy, and collaborating with various parties. This study provides a conceptual contribution to the development of Islamic educational leadership that is adaptive, innovative, and oriented towards improving the quality of madrasah education.